Epidemiology and Genetics of Mucopolysaccharidosis Type VI in Russia - Voskoboeva, Elena; Semyachkina, Alla; Miklyaev, Ochir; Gamzatova, Amina; Mikhaylova, Svetlana; Vashakmadze, Nato; Baydakova, Galina; Omzar, Olga; Pichkur, Natalia; Zakharova, Ekaterina; Kutsev, Sergey (Frontiers in Molecular Biosciences, 2022)
Mucopolysaccharidosis VI (MPS VI) is an autosomal recessive lysosomal storage disease caused by mutations in the arylsulfatase B gene (ARSB) and consequent deficient activity of ARSB, a lysosomal enzyme involved in glycosaminoglycan (s) (GAGs) metabolism. Here we present the results study of ARSB DNA analysis in MPS VI patients in the Russian Federation (RF) and other republics of Former Soviet Union. In a cohort of 68 patients (57 families) with MPS VI, a total of 28 different pathogenic alleles were found. The most prevalent nucleotide changes included c.194C>T (Ser65Phe) and c.454C>T (Arg152Trp). Five pathogenic alleles were novel, not previously reported (с.304C>G, c.533A>G, c.941T>C, c.447_456del10, С.990_1003del14). The nucleotide variant c.454C>T (Arg152Trp) was prevalent allele among Slavic Russian patients. The nucleotide variant c.194C>T (Ser65Phe) was found only in MPS VI families from the Republic of Dagestan. Based on the analysis of dry blood spots (DBS) collected from newborns in this RF region we showed the frequency of this mutant allele in the Republic of Dagestan to be 0.01 corresponding to the MPS VI frequency of nearly 1:10000, which is one of the highest worldwide. This may eventually make selective asymptomatic carrier test and newborn screening highly feasible in this region of the country.